PROBLEMATIKA KEDUDUKAN TAP MPR DALAM UU NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Tyan Adi Kurniawan; Wilda Prihatiningtyas (Universitas Airlangga, 2012)
The shift from a parliament supremation to constitution supremation after the reformation brought a basic change in the state structur of Indonesia. MPR is not the highest institution of this country but has become a higher institution and has an equal position as other higher institutions. It has become the main reason of not putting MPR/S’ law’s products up as in the law hierarchy in Indonesia based on Law Number 10/2004. However, Law Number 12/2011 put MPR’s decision in the hierarchy has made a new problematique. First of all, as seen on its position is above the laws and below the constitution. Second, the validity of MPR’s decision in the Law Number 12/2011. Third, related to which institution that has authority to examine MPR’s decision when it contradicts to Indonesian constitution.Key Word : TAP MPR, Position, Law Status, Authority of Examination